Do rap aos "Contos Crespos", de Luiz Silva (Cuti): a voz da resistência em sala de aula - Rosso, Donete Simoni (2016)
This research consists of a study focused on literature and teaching, with interfaces in reading, writing and interculturality. We intend to analyze the relevance of working activities of reading and writing with students in a the ninth grade of elementary school, based upon national rap lyrics and tales from Luiz Silva (Cuti), specifically those ones in the book Contos Crespos (2008), with a view to develop or foster the criticality and the emancipatory reading. It consists of a bibliographical research; along with a practical propose of activities in the classroom. As for the technical procedures, it fits an action research with qualitative approach. It involves the use of standardized data collection techniques: it is a documentary analysis of interpretation activities and textual productions- rap lyrics and critical-reflective comments according to Didactic Unit drafted during the master's degree specifically for this purpose. We waited, with this proposal, encourage the intercultural debate in the classroom with the support of aesthetic forms drawn up by subject historically silenced, such as rappers and afro-descendent writers, as well as motivate teachers possible readers of this essay to try the experience such a possibility of pedagogical approach and with this deepen, the theme of this research in other biases. The theoretical approach is focused on the design of language and literature as social practice, since these are born of the needs of social interaction and questioning political, social, economic among the speakers, supported by Bakhtin (1997/2003/2010) and in reading literacy, as advocated by Soares (2001/2006) Kleiman (1995/2006) and Rojo (2009). Reading strategies based on the recepcional method proposed by Aguiar and Bordini (1993) and Zilberman (1989) are based on Reader-Response Criticism, according to Jauss (2002). The theoretical bases of the process of reading and reader training count on the contribution of Lajolo (1997/1999), Orlandi (1988), Silva (2005) and Zilberman (1982). In literary issues, it was seek support in Bosi (1986), Candido (1972/2004), Cortázar (2006), Compagnon (2009), Rosenfeld (1976), Barthes (2007), Petit (2008), Abreu (2006), Gotlib (2006), Cuti (2010), Andrade (1999), Proença Filho (2004), Duarte (2014) and Bernd (1997/2011), among others